2017
DOI: 10.5812/mejrh.14594
|View full text |Cite
|
Sign up to set email alerts
|

Translation, Face and Content Validity of the Persian Version of School Function Assessment

Abstract: Background: School function assessment (SFA) is a criterion-referenced assessment that uses functional tasks to determine the level of participation and performance of students. The purpose of this study is to assess the face and the content validity of the Persian version of SFA for normal Iranian 6 -12-year-old children. Methods: This study has a methodological and psychometric design. We used a standard protocol, international quality of life assessment (IQOLA), for translating the SFA test. This protocol i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This agreement showed that all phrases in the Persian version of SFA are simple, meaningful, and clear. In the Iranian version of SFA, which is performed in normal schools, content validity is reported to be high (15). The Chinese version was performed in cerebral palsy children recently and showed high enough content validity, too (13).…”
Section: Discussionmentioning
confidence: 99%
“…This agreement showed that all phrases in the Persian version of SFA are simple, meaningful, and clear. In the Iranian version of SFA, which is performed in normal schools, content validity is reported to be high (15). The Chinese version was performed in cerebral palsy children recently and showed high enough content validity, too (13).…”
Section: Discussionmentioning
confidence: 99%
“…The content validity results showed that five item's score was lower than the acceptable score (< 0.7). Their final results indicate the appropriate content and formality of this tool (10) The reliability of this tool was tested by Rahimzadegan et al in 2017. On children with physical disability 80 students aged 6 -12 years old were evaluated and SFA was completed by parents and teachers of students.…”
Section: Discussionmentioning
confidence: 99%
“…The Cronbach's alpha coefficient for the different parts of this tool was excellent (0.84 < alpha < 0.99). The test-retest reliability of the test was good for the subtest of this tool (0.85 < ICC < 0.99) (29)(30)(31). The SFA includes 320 items categorized into three sections as follows: participation, task support, and activity performance.…”
Section: School Function Assessment (Sfa)mentioning
confidence: 99%